2021
DOI: 10.1016/j.jvir.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Superior Rectal Artery Embolization for Symptomatic Grades 2 and 3 Hemorrhoidal Disease: 6-Month Follow-up among 43 Patients

Abstract: Purpose: To assess the technical and clinical success rates of superior rectal artery embolization in the treatment of symptomatic Grades 2 and 3 hemorrhoidal disease.Materials and Methods: Since March 2019, 43 patients (24 men and 19 women; mean age, 52 years [18-77 years]) with symptomatic hemorrhoidal disease have been treated and completed the 6-month follow-up with anamnestic questionnaire and disease scores, including French bleeding, Goligher prolapse, visual analog scale for pain, and quality of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our findings demonstrate that the benefit of Emborrhoid was not associated with the hemorrhoidal, probably due to the small size of the study cohort. However, in a previous study, we reported that Emborrhoid was more effective in grade 2 than in grade 3 hemorrhoids, with 84% vs 50% of symptoms resolution, respectively at the 6 mo follow-up[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings demonstrate that the benefit of Emborrhoid was not associated with the hemorrhoidal, probably due to the small size of the study cohort. However, in a previous study, we reported that Emborrhoid was more effective in grade 2 than in grade 3 hemorrhoids, with 84% vs 50% of symptoms resolution, respectively at the 6 mo follow-up[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were a Goligher score of IV, pregnancy, previous hemorrhoidal surgery, inflammatory bowel disease. Use of anticoagulants or anti-aggregants was not considered an exclusion criterion[ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In most of the published series, technical success rates of 90–100% have been reported, while clinical success rates range from 63% to 97% [ 11 , 12 , 16 , 17 , 18 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. However, it is difficult to compare the results from the different series as there is no single and homogeneous criterion and standard that defines clinical success [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once fasting and adequate hemostasis are confirmed, the procedure is performed under aseptic conditions in a room equipped with a digital angiography. Conscious sedation is used, and local anesthetic is injected at the puncture site, which most commonly is the right femoral artery [25][26][27][28][29][30].…”
Section: General Techniquementioning
confidence: 99%
“…Coils are the most often documented embolic material; regardless, the usage of particles and coils is preferred by some working groups. Previous injection of 300-500 µm polyvinyl alcohol (PVA) particles within the distal part of SRA branches, near the CCR; followed by coil embolization of the SRA branches themselves, may close hemorrhoid plexus more distally and obstruct persistent MRA anastomoses, as shown in Figure 2 (Table 4) [25][26][27][28][29][30][31][32]. A recent study showed that larger microspheres (900-1200 µm) have better long-term efficacy and no minor ischemic complications compared with smaller sizes [33].…”
Section: General Techniquementioning
confidence: 99%